Empowering Coloring Program at Preschool Pelita, Tumbang Randang Village, Timpah Sub-District - Sisianti, Dian; Sinaga, Mei Minarni; Yuyun; Susida; Munte, Alfonso (Salus Publica: Journal of Community Service, 2023)
In Desa Tumbang Randang, a significant number of children struggled to distinguish and correctly color pictures or sketches. Recognizing coloring as a crucial skill for kindergarten children, a Community Engagement (PkM) initiative was launched. This program aimed to enhance children's coloring abilities, focusing on image texture sensitivity, finger adaptation, sensory awareness, and vocabulary expansion through the introduction of colors and image types. The research assessed children's development before and after participating in guided coloring activities. Initial observations noted that some children were rarely involved in such activities. The project's dream was to enable children to competently apply color combinations. During the design phase, mentors physically guided the children's hands, teaching them to color within boundaries. The define phase involved observing each child's color combination skills and their ability to express these on paper. This initiative, running from August 7 to 11, 2023, also aimed to benefit parents, locals, and village officials. It was conducted by IAKN Palangka Raya students through a cross-program educational approach. The results indicated improvements in the children's abilities to color pictures, compare and combine colors, and articulate color names using colored pencils. Additionally, the children exhibited increased independence and self-confidence, as evidenced by their artwork displayed on walls, celebrating their creative achievements.